Sistem Monitoring Ph Dan Suhu Air Pada Tambak Udang Menggunakan Protokol Websocket - Adhi Kurniawan; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Wireless Sensor Network (WSN) is a network architecture in which each sensor has the ability to be able to observe the surrounding conditions (sensing). In implementing the Wireless Sensor Network (WSN) we can create a monitoring system consisting of several sensors, microcontrollers and wireless communication between nodes with low and low power in maintaining them. To make communication between nodes, a network protocol is needed that is easily developed and understood by most users and can display information in real time, communication that can be used to create realtime applications, namely Websocket. Websocket is chosen for communication between nodes because it is able to provide statefull and full-duplex communication on the HTTP protocol which is very suitable for monitoring systems. In its implementation the system is used to monitor the pH and temperature of the water in the cultivation of shrimp ponds. The results of performance testing show that the accuracy of the sensor in obtaining information on the pH value and temperature has an accuracy rate of 99% with an error rate compared to other measuring devices which are below 1%. While the data transmission performance required by the system in serving requests from the client until sending it back to the client requires an average time of less than 1 second of each transmission process.